Teknik Penggerombolan Fuzi untuk Pewilayahan Curah Hujan di Sentra Produksi Padi - Aris Pramudia; Vonny Koesmaryono; Irsal Las; Tania June; I Wayan Astika (Jurnal Ilmu Pertanian Indonesia, 2007)
Rainfall zoning analysis with fuzzy clustering method has been performed at the centre of paddy area in the northern coast of Banten Province and West Java Province. Rainfall data recorded in the 1980-2006 period from 62 rainfall stations in the northern coast of Banten Province and from 75 rainfall stations at Karawang and Subang in the northern coast of West Java Province have been used in this analysis. For the first analysis a calculation of arithmetic mean values representing EI-Nino, La-Nina and Normal condition has been performed. Next, a fuzzy clustering analysis is applied to these mean values. The clustering analysis consists of two steps. First, a symmetric and reflective compatibility relation matrix describing a distance function between rainfall stations is calculated. Second, a fuzzy equivalency relationship i.e. a transitive approach of fuzzy compatibility matrices is determined. The results of analysis indicate a difference in the equivalency level among the stations under the EI-Nino, La-Nina and Normal conditions in the northern coast of Banten Province and West Java Province. Based on the 75°/o equivalency level, in the northern coast of Banten area can be grouped into four rainfall zones under EI-Nino condition, two zones under La-Nina condition and three zones under Normal condition. On the other hand, in the northern coast of West Java area can be grouped into three zones under EINino condition, two zones under La-Nina condition, and four zones under Normal condition.Keywords: Arithmetic means values, EI-Nino, La-Nina, Fuzzy clustering, Rainfall zoning